Leaching of a Mongolian chalcopyrite concentrate - Welham, Nicholas J; Temuujin, Jadambaa; Setoudeh, Nader (Mongolian Journal of Chemistry, 2018)
A Mongolian chalcopyrite flotation concentrate was leached using sodium hypochlorite adjusted to different pH using hydrochloric acid. It was found that using a starting pH of below 5.0 resulted in more efficient leaching. The extent of chalcopyrite leaching was determined by the concentration of sodium hypochlorite with > 40% dissolution being achieved. The residue after leaching was found to consist primarily of unreacted chalcopyrite which would be suitable for further leaching or smelting.